Standardization of Snakehead Fish (Channa striata) Concentrates Obtained from Sungai Itik Village, Kubu Raya District, West Kalimantan - Aulia, Yunita Hananda; Andrie, Mohamad; Wintari , Wintari (Universitas Ahmad Dahlan, 2024)
Standardization is the method of identifying properties based totally on superb parameters to advantage the identical diploma of satisfaction. it has been proven that vitamins decided in snakehead fish (Channa striata) from herbal assets can be implemented as a possibility to hasten the recuperation of wounds. With the assistance of the techniques of freeze drying, this examination sought to set up the standardization of snakehead fish pay attention from Sungai Itik Village in Kubu Raya Regency, West Kalimantan as an uncooked material for prescribed drugs that treat wounds. Standardization carried out on concentrate samples consisted of specific and non-specific parameters. Specific parameters consist of organoleptic, water-soluble essence content, protein, and albumin. While the non-specific parameters tested were moisture content, ash content, acid-insoluble ash content, and drying shrinkage. The test results showed that the water content contained in snakehead fish was 7.21% ± 0.165, ash content was 10.47% ± 1.06, acid insoluble ash content was 1.40% ± 0.115, water-soluble essence content was 77.10% ± 0.54, dry shrinkage rate was 13.973% ± 0.193, the protein was 99.49% and albumin was 7.03 g/dl. The standardization parameters have not met all the tests so it can be said that snakehead fish concentrate has not met the standard and has not been standardized for natural wound healing medicinal ingredients.